Morphological Analysis of Ciplukan Plant (Physalis angulata L.) Pollen for Macroscopic Identification - Fendy Prasetyawan; Yuneka Saristiana; Faisal Akhmal Muslikh; Hasriyani Hasriyani; Yunita Dian Permatasari (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
This research addresses the prevalence of arthritis in Indonesia, focusing on traditional medicinal plants like Ciplukan due to the side effects of synthetic treatments. Arthritis, affecting 23.6-31.3% of the population, with Osteoarthritis (50-60% in the elderly) being the most common, necessitates alternative, less toxic remedies. Traditional medicine, relying on plant-derived remedies, is explored for its accessibility, affordability, and lower side effects. The study delves into Ciplukan, known for its anti-arthritis properties, conducting in vitro tests on its methanol extract. Results reveal anti-arthritis activity attributed to steroids, flavonoids, and alkaloids. The methodology involves macroscopic and microscopic examinations of Ciplukan plants, verifying authenticity and confirming the accuracy of plant samples. Organoleptic assessments highlight distinctive features, contributing to the plant's identification. Microscopic examination reveals the presence of stomata and palisade cells in the upper epidermis, aligning with literature data. The vascular system analysis emphasizes the efficiency of resource transport and adaptation to environmental changes. In conclusion, the study provides a comprehensive understanding of Ciplukan's characteristics, supporting its potential in arthritis treatment. The findings contribute to the utilization of traditional medicine in healthcare, emphasizing the importance of plant-based remedies with fewer side effects.